Rancang Bangun Alat Pengering Otomatis pada Proses Produksi Rumput Laut yang Dikendalikan oleh Smartphone - Meriyatul Lusidah (Jurnal Jaringan Telekomunikasi, 2018)
In the majority of the seaweed drying process is still using the traditional method by drying it in the sun on a waring. Based on these problems, it is necessary to have a combination of energy in the drying process of seaweed so that drying of the seaweed can be more efficient and save time. The results of designing and testing the tool as a whole can run and the sensor can detect the value of temperature and humidity. The android application can run and activate the dryer system and turn off automatically when it reaches a humidity below <28%. Conclusion in testing the accuracy of the DHT22 sensor with a hygrometer measuring instrument, the average temperature value during the day is 30,365 ° C hotter than the nighttime temperature of 27.75 ° C. The average value of humidity at night is 66.35% cooler than the humidity at daytime of 60.45%. So it can be concluded that the temperature during the day is hotter than the temperature at night. And the humidity at night is cooler than during the day. For the delay is higher at 18:00 at night using the Indosat operator, which is 1.0545ms than the Axis operator, which is 1.0185ms. Meanwhile, throughput is greater at 12:00 noon when using the Axis operator, which is 7,497 Kbit / Sec than the Indosat operator, which is 1.7245Kbit / Sec.